Disciplinary Liability of Judges – Prevention or Encouragement (Law and world, 2021)
Present paper is intended to verify how strongly the current legislation of Georgia is focused on prevention of disciplinary misconduct of judges. The matter is discussed through the prism of the concept of general prevention (Die generalpräventive Lehre). After a consistent review of legislation, following conclusion should be made: • The main idea of the general prevention – the threat of punishment – is diminished. • Current Georgian legislation is less than focused on general prevention of disciplinary misconduct of judges; • Current regulations make it even more difficult to prevent misconducts; • A deep comprehension of the matter through the prism of concept of general prevention is needed in order to create new, more acceptable regulations. The discussion offered in this paper has once again stressed on an ever existing problem: It is not necessary at all that a concept developed within certain field of law is used in a restricted way − only within the frame of that same field of law. It should be applied in process of comprehension of a problem that occurred within adjacent field of law if it is applicable considering its subject, problematics or/and methodological base.